2013
DOI: 10.1177/0020764013502318
|View full text |Cite
|
Sign up to set email alerts
|

Social interaction among people with psychiatric disabilities – Does attending a day centre matter?

Abstract: Background: Engaging in social interaction has, for people with psychiatric disabilities, been shown to enhance well-being and the experience of meaning and to generally prevent the worsening of mental illness. Aim: The aim of the study was to investigate how day centre attendees differed from non-attendees regarding different aspects of social interaction and to investigate how occupational factors, including day centre attendance, and previously known predictors were related to social interaction in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…According to previous research, such a match has been found to be vital for client satisfaction and engagement (Leufstadius, Eklund, & Erlandsson, 2009;Rebeiro & Cook, 1999;Tjörnstrand et al, 2011). Finally, since research has shown that one of the main advantages with attending a day center is an increased number of social contacts (Argentzell et al, 2013) one can also expect a change in that respect. It could thus be anticipated that the day center attendees' ratings of empowerment, social contacts and satisfaction with the day center services would improve with the free choice reform.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to previous research, such a match has been found to be vital for client satisfaction and engagement (Leufstadius, Eklund, & Erlandsson, 2009;Rebeiro & Cook, 1999;Tjörnstrand et al, 2011). Finally, since research has shown that one of the main advantages with attending a day center is an increased number of social contacts (Argentzell et al, 2013) one can also expect a change in that respect. It could thus be anticipated that the day center attendees' ratings of empowerment, social contacts and satisfaction with the day center services would improve with the free choice reform.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, comparative studies have shown that day center attendees tend to have more valued activities than non-attendees, but that they were not more satisfied with everyday activities in general (Argentzell, Leufstadius, & Eklund, 2012). The day center attendees also had a larger number of social contacts in general, but not more close ones (Argentzell, Leufstadius, & Eklund, 2013). A conclusion might thus be that effective day centers promote empowerment, activity and social interaction, and when evaluating the outcomes of reforms and other types of interventions these variables would be adequate outcome measures.…”
Section: Introductionmentioning
confidence: 98%
“…Negative internalized perceptions result in fear, apathy, low self‐esteem, and meaninglessness (Hinshaw & Cicchetti, ; Perlick, ). As a result, these individuals occupy devalued roles in society, remain isolated from mainstream society, and excessively rely on mental health professional caregivers for social connections (Argentzell, Leufstadius, & Eklund, ; Tsai, Desai, & Rosenheck, ).…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction with daily occupations was the dominant variable in explaining different QOL domains, especially the specific domains’ satisfaction with leisure and work, and the summed satisfaction with all life domains (QOL Index). A further study comparing DC attendees with nonattendees found no differences regarding any aspects of QOL .…”
Section: Introductionmentioning
confidence: 85%